On starlike functions related with the convex conic domain - Kargar Rahim; Sokol Januz (SEMNAN UNIV, 2022)
In the present paper, we study a new subclass M-p (alpha,beta) of p-valent functions and obtain some inequalities concerning the coefficients for the desired class. Also, by using the Hadamard product, we define a new general operator and find a condition such that it belongs to the class M-p (alpha,beta).